Perencanaan Kawasan Agrowisata Di Taman Maccini Sombala Kota Makassar - Fadhil Surur; Rizqi Auliyah (Politeknik Pariwisata Makassar, Indonesia, 2020)
Agrotourism is a form of tourism activities that utilize agro business as a tourist attraction with the aim to expand knowledge, travel, recreation, and business relationships in the field of agriculture. Development of agro-tourism management especially in urban areas requires close cooperation between various sectors, namely transportation sector, tourism sector, agriculture sector, trade sector, regional development sector and so on. The presence of Taman Maccini Sombala in Makassar City becomes a place to fulfill the needs of green open space (public open space). In line with the development of this potential has not been fully utilized both for the fulfillment of food needs of society and the main function as a public space and tourist space. This role then developed into an agro-tourism area of the city. Assessment in measuring MoI Park development program as one of agro-tourism in Makassar by looking at the existing condition, analyzing the suitability and feasibility of agrowisatanya and how the carrying capacity both physically and with the consideration of the manager and also the development concept that can be applied in Taman Maccini Sombala of Indonesia as object of agro tourism city.